Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0139-001 Telephone: Maida Vale 1384. Dr. H.B. MORGAN. 4, Aberdare Gardens, Hampstead, LONDON, N.W.6. 4th January, 1937. Captain J.R. White, 8, Torrington Square, LONDON. W.C.1. Sir, I beg to acknowledge receipt of your letter of the 21st December, which only reached me on the 26th December last. Owing to the holidays I am only able to acknowledge it to-day, and I will be writing you an answer within a short time. I would like to say at once that I do not agree with the account you have given of the interview you had with me at my house, or your interpretation of the action I have taken, and I rather resent your observation that I am under Communist influence. An accusation of that kind, in view of the work I have done and the straightforward way in which I have taken my part in the Spanish Medical Aid Committee, can only be strongly repudiated and reprobated. Yours faithfully, H.B.M. E.K. 292C/946/2/139